Reducing and deducing the structures of consciousness through meditation - Katyal, Sucharit (Frontiers in Psychology, 2022)
According to many first-person accounts, consciousness comprises a subject-object structure involving a mental action or attitude starting from the “subjective pole” upon an object of experience. In recent years, many paradigms have been developed to manipulate and empirically investigate the object of consciousness. However, well-controlled investigation of subjective aspects of consciousness has been more challenging. One way, subjective aspects of consciousness are proposed to be studied is using meditation states that alter its subject-object structure. Most work to study consciousness in this way has been done using Buddhist meditation traditions and techniques. There is another meditation tradition that has been around for at least as long as early Buddhist traditions (if not longer) with the central goal of developing a fine-grained first-person understanding of consciousness and its constituents by its manipulation through meditation, namely the Tantric tradition of Yoga. However, due to the heavy reliance of Yogic traditions on the ancient Indian Samkhya philosophical system, their insights about consciousness have been more challenging to translate into contemporary research. Where such translation has been attempted, they have lacked accompanying phenomenological description of the procedures undertaken for making the precise subject-object manipulations as postulated. In this paper, I address these issues by first detailing how Tantric Yoga philosophy can be effectively translated as a systematic phenomenological account of consciousness spanning the entirety of the subject-object space divided into four “structures of consciousness” from subject to object. This follows from the work of the 20th century polymath and founder of the Tantric Yoga school of Ananda Marga, Prabhat Ranjan Sarkar, who expounded on the “cognitivisation” of Samkhya philosophy. I then detail stepwise meditation procedures that make theoretical knowledge of these structures of consciousness a practical reality to a Tantric Yoga meditator in the first-person. This is achieved by entering meditative states through stepwise experiential reduction of the structures of consciousness from object to subject, as part of their meditative goal of “self-realisation.” I end by briefly discussing the overlap of these putative meditation states with proposed states from other meditation traditions, and how these states could help advance an empirical study of consciousness.